Selizitapia gen. nov. (Hemiptera: Fulgoromorpha: Flatidae) from tapia woodlands of Madagascar - Dariusz Świerczewski (European Journal of Taxonomy, 2021)
A new monotypic genus of flatid planthoppers (Hemiptera: Fulgoromorpha: Flatidae), Selizitapia gen. nov., is described for Selizitapia pennyi gen. et sp. nov. (type species) from the island of Madagascar. Habitus, male and female external and internal genital structures of the new species are illustrated and compared with similar taxa. Selizitapia pennyi gen. et sp. nov. is endemic to Madagascar where it is known to date only from one locality in the Central Plateau and is associated with tapia woodland formation.